Models for evaluating the level of development of destinations. Recommendations for the destination Cuba - Contino Rodríguez, Diana (2024)
The study of the level of development of destinations helps to understand the evolution of tourist spaces, serving as a basis for managers to design strategies that increase their competitiveness. The background information on the website indicates that in Cuba the sector is not managed under an approach or model applicable to the current reality and there is a lack of a tool that allows, as part of strategic planning, to evaluate the level reached by specific destinations. Therefore, the general objective of this research was to propose guidelines for a model that allows the evaluation of the level of development of Cuban tourist destinations. The applied methodology consisted of two phases that combine several tools where expert interviews and bibliographic review predominate. The main results allowed us to identify that the most internationally recognized models have different strengths and weaknesses; their effectiveness will depend on the adaptation to the characteristics of the destination where it is applied. The last phase of the research allowed us to propose the Three-Phase Development Model as a model most adjusted to the current reality of the destination, although for its implementation other research must be carried out where adjustments are made to the current proposal.